Behavior of organic contaminants in permafrost-affected soils - Zschocke, Anne (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2015)
Soils and soil functions are a main resource for our existence on earth. But soils are under threat by degradation. Another resource that seems irreplaceable for human being on this planet is oil. Oil, as well as soil, is a non-renewable resource in relation to human life time. With decreasing reservoirs in the established oil production areas, remote oil resources, like in the Arctic, come into the focus of exploration activities (Bird et al. 2008). Exploration, transport and processing of oil inevitably cause accidental spills and continuous release of product and compounds into the soil on different levels. In general the reasons are technical inadequacy, human error or natural hazards (Siciliano et al. 2008). Some studies found that the entry of organic contaminants in permafrost-affected soils led to an increase in active layer thickness and subsequent soil subsidence (Collins et al. 1993). In Antarctic soils the accumulation of PAHs from atmospheric deposition were found in the transient layer (Curtosi et al. 2007). To identify the processes responsible for organic contaminant migration in permafrost-affected soils a laboratory method to simulate the natural freezing process was invented and the distribution of different PAHs in oil contaminated soils at water unsaturated conditions were investigated. Experiments were run with a closed column system in three parallels and a reference. The columns were cooled from the bottom or from the top. The freezing process was monitored in each column by two temperature probes and a TDR probe. A two-phase freezing scenario proved to be the best way to simulate the natural freezing process in different soils with the along going water migration processes. Until now two main processes of organic contaminant migration dependent on the freezing process in soils have been identified. For organic contaminants that are present as a single phase, a pushing out of the soil pores forward the freezing front due to the freezing induced water migration and ice formation has been ...